If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 = 58 + -3x Reorder the terms: 18 + 2x = 58 + -3x Solving 18 + 2x = 58 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 18 + 2x + 3x = 58 + -3x + 3x Combine like terms: 2x + 3x = 5x 18 + 5x = 58 + -3x + 3x Combine like terms: -3x + 3x = 0 18 + 5x = 58 + 0 18 + 5x = 58 Add '-18' to each side of the equation. 18 + -18 + 5x = 58 + -18 Combine like terms: 18 + -18 = 0 0 + 5x = 58 + -18 5x = 58 + -18 Combine like terms: 58 + -18 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| -45+7X=32 | | 3x+6=26-2x | | 8x=16+-4x | | 8x=16+-4 | | 10x=60-10x | | 4x-12x^2=0 | | t(t+2)(t-2)+2=0 | | t^3-4t+2=0 | | 2X-22=10 | | X+25=36 | | -7x=14+5x | | -7x=14+5 | | -25+8+X=10 | | 9f=3f-4 | | 138-3x=24x+21 | | x+(x+1)+x^2=64 | | 5x=10+-15x | | 60+x=56+18 | | 5x=10+-15 | | 60+x=56 | | 9b-3b= | | 3x+7=2.5 | | x+(x+1)+x^2=63 | | 3q-1=q+3 | | 127=2.4471x+22.547 | | 6x=12-3x | | 8x-4=4x-3 | | 5x-7+2*(3-5x)=-x+2 | | 127=4.4571*x+3 | | 7x+30x+4*(8x+1)=2*(22x+15)-1 | | 7x+30x+4*(8x+1)=2*(22x+15) | | 7x+30x+4*(8x+1)=2*(22x+15)+3 |